PERANAN INFORMASI PERTANIAN PADA PETANI KELAPA DI KELURAHAN PANDU KECAMATAN BUNAKEN KOTA MANADO - Pinanus ., Werenengga; Elsje Pauline Manginsela; Melsje Y. Memah (Sam Ratulangi University, 2018)
This study aims 1. Know the role of agricultural information in increasing the production and income of coconut farmers. 2. Identify sources of information from which coconut farmers obtain agricultural information. Place of study is Pandu Village Bunaken Sub-District Manado City. This research was conducted for three months, ie from August to October 2017. This study uses primary data and secondary data. Primary data were obtained from 10 coconut farmers using questionnaires. While the secondary data obtained from the Office of Village Pandu Bunaken Manado City. Sampling method in this research using purposive sampling method that is those who belong to upper layer farmers. The results showed 1. The role of agricultural information obtained by coconut farmers that to obtain good production and income is by the processing of land, pest plants, seeds, fertilizers, pesticides, production and processing and transport of copra. 2. Sources of agricultural information obtained by coconut farmers is information from fellow farmers and agricultural extension workers.